Pol??tica monet??ria e o mercado imobili??rio brasileiro: uma abordagem SVAR - Vieira, Juliana Saad (2019)
The present study analyzes interdependent effects between Brazilian monetary policy and real estate market, using a structural VAR model (SVAR) and its impulse response functions for diagnosis. In the face of the recent Brazilian economic crisis, the development of more extensive studies on correlated movements of interest rates and the price of real estate assets is relevant, since in other countries, variations in the interest rate and shocks from real estate variables were responsible for disturbances and / or transmission of these over other macroeconomic indicators. In addition, the literature emphasizes that monitoring of these is crucial, given its predictive nature on oscillations, contributing to the formulation of effective monetary policies. Also, the analysis is extended to a VECM model, given the presence of cointegration. The results of the different models converge, indicating a tenuous relationship between interest rates and real estate variables in the long term. Corroborating the theory employed, the variable proxy for real estate investment declines after restrictive monetary shocks. However, real estate prices, in all scenarios, respond little significantly, reinforcing inexpressive correlation between monetary policy and real estate market prices, especially in the long run.